Chemical Quality of Fresh New Zealand White Rabbit Meat in Batu, Indonesia. Issue 1 (April 2020) - Fadlilah, A; Rosyidi, D; Susilo, A
Abstract: Batu was one of the cities in the province of East Java, Indonesia that one of the leading tourist cities in Indonesia. Rabbit satay was one of the Batu city famous foods. Many tourists visited Batu City for consume it. Rabbits were obtained from rabbit breeders in the Batu city. The environment and the pattern of rearing rabbits had an impact on the quality of the meat and specific characteristic of the meat production. This study aimed to determine the chemical quality of the fresh New Zealand White (NZW) rabbit meat in the Batu City using the proximate analysis. This Research used 9 males of NZW rabbits, each of them was taken 100gr of loin flesh for proximate analysis. Rabbits were kept intensively. The results showed that fresh NZW Rabbit Meat had a carbohydrate content was 0.43%, Protein content was 19.99%, Moisture was 75.84%, Ash content was 1.43% and Energy gross was 110.47 Kcal/100g.